The Effect of Transformational Leadership and Work Motivation of Teacher Discipline in State Elementary School in Kayong Utara - Suhaimi Mandala; Uray Husna Asmara; Fadillah Fadillah (Universitas Tanjungpura, 2019)
This study aims to determine Transformational Leadership to increase work motivation to teachers so that the creation of work discipline Teachers of Public Elementary Teachers In Sukadana District Kayong Utara District. This research is a quantitative study with data collection using a data collection tool in the form of a questionnaire or questionnaire. The subjects of this study were all 115 elementary school teachers in Sukadana Subdistrict, North Kayong Regency with the characteristics of civil servant status, having a minimum working period of 2 years and maximum age of 55 years. The conclusions of this study are as follows: (1). Principal transformational leadership has a positive effect on teacher work discipline (B = 0.760; sig. 0.006 <0.05). (2). Teacher work motivation has a positive effect on teacher work discipline (B = 0.773; sig. 0,000 <0.05). (3). Transformational leadership (X1) and work motivation (X2) simultaneously affect teacher work discipline (Y). It is known from the value of sig. is 0,000 <0.05, and the results of the Fcount value is 82.232> Fable 3.08. The value of R square is 0.595 or equal to 59.50%. The number implies that the Transformational Leadership (X1) and Work Motivation (X2) variables simultaneously influence the Teacher Work Discipline variable (Y) of 59.50%. While the remaining 40.5% (100% - 59.50%) is influenced by other variables. Suggestions of this research are: (1) the principal must be able to act wisely towards his subordinates, conversely the teacher must also always increase dedication, obedience, loyalty, adherence to the rules set by the principal; (2) the conditions of teachers' working motivation that is already good needs to be maintained and improved in ways such as giving rewards, implementing group structure tasks and empowering teachers; (3) the work discipline of teachers needs to be improved by applying applicable work rules and procedures. The enforcement of discipline should also be from the teacher himself.Keywords: Transformational Leadership, Work Discipline, Work Motivation